Effect of Regioisomerism on the Efficiency of 1-Phenylpyrrole-Type Atropisomeric Amino Alcohol Ligands in Enantioselective Organometallic Reactions - Mátravölgyi, Béla; Deák, Szilvia; Erdélyi, Zsuzsanna; Hergert, Tamás; Ábrányi-Balogh, Péter; Faigl, Ferenc (Synlett, 2018)
Syntheses of two regioisomeric series of atropisomeric amino alcohols and a comparative study on their application in the enantioselective addition of diethylzinc to benzaldehyde are reported. Systematic modification of the electronic and steric properties of the functional groups resulted in highly efficient catalyst ligands in both series. Quantum-chemical calculations agreed well with the experimental results of this first systematic comparative study on regioisomeric atropisomeric ligands.
Keywords: atropisomerism; amino alcohols; enantioselectivity; asymmetric catalysis; phenylpyrrole; ligands